A fluorogenic peptide-based smartprobe for the detection of neutrophil extracellular traps and inflammation. Issue 1 (17th December 2020) - Rios, Maria R.; Garoffolo, Gloria; Rinaldi, Giulia; Megia-Fernandez, Alicia; Ferrari, Silvia; Robb, Calum T.; Rossi, Adriano G.; Pesce, Maurizio; Bradley, Mark
Abstract : A highly specific, fluorogenic probe detects human neutrophil elastase (hNE) in activated neutrophils and Neutrophil Extracellular Traps (NETs). Abstract : A highly sensitive optical probe for the detection of activated neutrophils and Neutrophil Extracellular Traps (NETs) is reported. It is based on a triple-quenched, super-silent tri-branched probe that generates >20 fold increase in fluorescence upon cleavage. The probe was highly specific for human neutrophil elastase, a protease that mediates a variety of inflammatory diseases, and detected NETosis and neutrophil activation in in vitro differentiated neutrophils and isolated human neutrophils.